Lean Production Model to Reduce Defects and Achieve Sustainability in a Peruvian Textile SME - Camones-Caballero, Vierochka (2024)
Currently, SMEs are exposed to economic losses due to inadequate internal management, one of the main being "Process Management". This brings consequences to the entire flow of production and sales of the company in a directly proportional way. Also, without the necessary material to produce, there are no products to sell, affecting the level of defective and customer satisfaction. Therefore, the motivation of the article is to design the management by processes and analyze the causes of the increase in the levels of defective in the SMEs of the Peruvian textile sector. To address this challenge, it aims to reduce the level of defective products from 8% to 5% optimal as indicated by the technical gap. The solution integrates Lean tools such as the 5S tool, Autonomous Maintenance and Process Standardization to improve and increase quantitative and qualitative indicators in the company. In addition, the PDCA cycle was integrated as a fundamental contribution and link to the proposed solution model and also as a mechanism to support sustainability that will be implemented and that allows the continuous improvement of processes and product quality, which will increase the competitiveness and profitability of the company in the market